Konsep Regulasi Berbasis Risiko: Telaah Kritis dalam Penerapannya pada Undang-Undang Cipta Kerja - Akhmad Yasin (Jurnal Konstitusi, 2021)
The Law on Job Creation emphasizes the ease of doing business. One of the things that is of concern is the simplification of business permit. The concept of risk-based regulation is attractive to simplify the programs due to the assumption that it may cut off a number of licenses. However, the application of risk analysis to screen permits is something different from other countries. In addition, the application of risk-based regulations also needs to pay attention to the critique that is not accommodated in the Law. This paper describes 4 (four) critiques of the application of risk-based regulation in the Law, (i) the omnibus format confuses risk assessment, (ii) volatility risk has not been considered, (iii) systemic risk has not been considered and (iv) potential “regulatory capture”. Conceptually, the application of risk-based regulation has sparked an academic discourse regarding the broad understanding of regulation that has evolved far from the narrow meaning in academic discourse in Indonesia which defines it only as a statutory regulation.